El impacto del neoliberalismo en Colombia y su incidencia en el ejercicio profesional del Trabajo Social - Yenny Andrea Belalcázar-Vásquez; Roberth Wilson Salamanca-Ávila (Eleuthera)
This text presents an analysis of how neoliberalism in Colombia has promoted structural transformations, intensifying social inequalities, conflicts, and the emergence of manifestations of the social question. These have generated tensions between the State and society. Therefore, Social Work has responded to the tensions between capital and social struggles by generating and participating in institutional responses from both the state and private sector. Professional action is focused on intervening with the population that social services are directed towards because of social policies.